PENGENDALIAN DEMAM BERDARAH DENGUE DENGAN OVITRAP DAN MOSQUITO TRAP DI BEBERAPA DAERAH DI INDONESIA - Vivin Mahdalena; Rahayu Hasti Komaria (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2021)
The Dengue Fever (DF)/Dengue Hemorrhagic Fever (DHF) is still a major public health problem in Indonesia. Indonesia of DHF cases in 2019 increased compared to the previous year, which was 138.127 cases with an Incidence Rate (IR) of 51.53 per 100.000 population. The vectors of dengue virus are Aedes aegypti, Aedes albopictus, Aedes polynesiensis, and Aedes scutellaris mosquitoes. Prevention of dengue transmission relies mainly through vector control. The use of traps such as ovitrap and mosquito trap has the potential to be applied and integrated with other methods. Ovitrap and mosquito trap usage information is expected to be applied in the community and can assist in the dengue vector control program. The data in this article were secondary data from several research results that had been published and were field experiment. Ovitrap and mosquito trap are able to trap Aedes and non-Aedes mosquitoes. The effectiveness of the trap can be increased through the use of attractants from plant-based ingredients in the form of straw soaking water, mixture of brown sugar and yeast, mixture of granulated sugar and yeast, and chili extract. Ovitrap and mosquito trap with attractants from plant-based ingredients were quite effective in reducing the density of Aedes mosquitoes, besides that it safer for humans and non-target animals.